Practical Guide for Designing Activities that Integrate Curricular Content, Computational Thinking and Constructionist Theory - Avila, Christiano Martino Otero; Cavalheiro, Simone André da Costa (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2022: Anais do XXXIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2022.225108, 2022)
This paper presents a practical guide to encourage professionals to reflect on aspects that must be considered for the elaboration of a didactic activity that integrates: a) promotion of curricular learning; b) development of Computational Thinking; and c) a constructionist learning environment. A proof of concept shows that the guide has the potential to instigate teachers of k-12 education in the development of activities with the proposed characteristics.